Integrative taxonomy documents two additional cryptic Erithacus species on the Canary Islands (Aves) - Sangster, George; Luksenburg, Jolanda A.; Päckert, Martin; Roselaar, Cees S.; Irestedt, Martin; Ericson, Per G. P. (Zoologica scripta, 2022)
The European Robin Erithacus rubecula is currently treated as a single species with eight subspecies. A previous molecular study and new molecular, morphometric and bioacoustic data reported here strongly support the recognition of three species in this complex: E. rubecula (Europe, North Africa and Macaronesia except the central Canary Islands), E. superbus (Tenerife) and a recently described subspecies on Gran Canaria which we raise to species rank as E. marionae. The taxa on Tenerife and Gran Canaria have previously been lumped as a single taxon but differ from each other and from E. rubecula in territorial songs, tic calls, seep calls and wing length. All three species are characterised by moderate to high levels of interspecific mitochondrial DNA sequence divergence (mean 4.2–4.8%). Phylogenetic analysis indicates that E. marionae is sister to E. superbus + E. rubecula. Recognition of Gran Canaria and Tenerife Robins as separate species adds two single‐island endemics to the Canary Islands avifauna.